Distinct functions and cooperative interaction of the subunits of the transporter associated with antigen processing (TAP) - Karttunen, Jaana T. (The National Academy of Sciences, 2001)
The ATP-binding cassette (ABC) transporter TAP translocates peptides from the cytosol to awaiting MHC class I molecules in the endoplasmic reticulum. TAP is made up of the TAP1 and TAP2 polypeptides, which each possess a nucleotide binding domain (NBD). However, the role of ATP in peptide binding and translocation is poorly understood. We present biochemical and functional evidence that the NBDs of TAP1 and TAP2 are non-equivalent. Photolabeling experiments with 8-azido-ATP demonstrate a cooperative interaction between the two NBDs that can be stimulated by peptide. The substitution of key lysine residues in the Walker A motifs of TAP1 and TAP2 suggests that TAP1-mediated ATP hydrolysis is not essential for peptide translocation but that TAP2-mediated ATP hydrolysis is critical, not only for translocation, but for peptide binding.